Examining the Relationship Between Adverse Childhood Experiences and ADHD Diagnosis and Severity - Crouch, Elizabeth; Radcliff, Elizabeth; Bennett, Kevin J.; Brown, Monique J.; Hung, Peiyin (Academic pediatrics, 2021)
Although prior research has examined the prevalence of ACEs among children with attention deficit-hyperactivity disorder (ADHD), little is known about the household and family settings of children with ADHD. Our study utilizes a recent nationally representative dataset to examine the association between adverse childhood experiences (ACEs), child and household characteristics, and ADHD diagnosis and severity. Using the 2017–2018 National Survey of Children's Health (NSCH), our sample consisted of children three years of age or older, as this is the youngest age at which the NSCH begins to ask caregivers if a child has been diagnosed with ADHD (n = 42,068). Multivariable logistic regression was used to examine the association between ACE type, score, and ADHD and ADHD severity, controlling for child and household characteristics. Children exposed to four or more ACEs had higher odds of ADHD (aOR 2.16; 95% CI 1.72–2.71) and moderate to severe ADHD (aOR 1.89; 95% CI 1.31–2.72) than children exposed to fewer than four ACEs. Other child characteristics positively associated with ADHD included age and public insurance; other Non-Hispanic races compared to Non-Hispanic White had lower odds of ADHD. Of children reported with ADHD, public insurance was also associated with caregiver-reported moderate to severe ADHD. Children with ADHD have a higher prevalence of ACEs, making this study important for understanding the relationship between ACEs and ADHD at the population level.